PI3K/Akt Pathway Contributes to Neurovascular Unit Protection of Xiao-Xu-Ming Decoction against Focal Cerebral Ischemia and Reperfusion Injury in Rats - Lan, Rui (Hindawi Publishing Corporation, 2013)
In the present study, we used a focal cerebral ischemia and reperfusion rat model to investigate the protective effects of Xiao-Xu-Ming decoction (XXMD) on neurovascular unit and to examine the role of PI3K (phosphatidylinositol 3-kinase)/Akt pathway in this protection. The cerebral ischemia was induced by 90 min of middle cerebral artery occlusion. Cerebral infarct area was measured by tetrazolium staining, and neurological function was observed at 24 h after reperfusion. DNA fragmentation assay, combined with immunofluorescence, was performed to evaluate apoptosis of neuron, astrocyte, and vascular endothelial cell which constitute neurovascular unit. The expression levels of proteins involved in PI3K/Akt pathway were detected by Western blot. The results showed that XXMD improved neurological function, decreased cerebral infarct area and neuronal damage, and attenuated cellular apoptosis in neurovascular unit, while these effects were abolished by inhibition of PI3K/Akt with LY294002. We also found that XXMD upregulated p-PDKl, p-Akt, and p-GSK3β expression levels, which were partly reversed by LY294002. In addition, the increases of p-PTEN and p-c-Raf expression levels on which LY294002 had no effect were also observed in response to XXMD treatment. The data indicated the protective effects of XXMD on neurovascular unit partly through the activation of PI3K/Akt pathway.